2020
DOI: 10.1177/1076029620902849
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Algorithm to Predict Mortality in Patients With Sepsis and Coagulopathy

Abstract: Sepsis is a systemic response to infection with a high rate of mortality and complex pathophysiology involving inflammation, infection response, hemostasis, endothelium, and platelets. The purpose of this study was to develop an equation incorporating biomarker levels at intensive care unit (ICU) admission to predict mortality in patients with sepsis, based on the hypothesis that a combination of biomarkers representative of multiple physiological systems would provide improved predictive value. Plasma samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 47 publications
(117 reference statements)
0
14
0
Order By: Relevance
“…During the process of fighting against viral or bacterial invasion, immune systems are inevitably activated, thus stimulating the coagulation system. 9,15 Thus, SARS-CoV-2 infection was also observed to cause disturbances of coagulation and immune systems, which are non-negligible issues during the treatment of COVID-19 patients. This study reveals that SARS-CoV-2-associated coagulopathy exists in almost all critically ill COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the process of fighting against viral or bacterial invasion, immune systems are inevitably activated, thus stimulating the coagulation system. 9,15 Thus, SARS-CoV-2 infection was also observed to cause disturbances of coagulation and immune systems, which are non-negligible issues during the treatment of COVID-19 patients. This study reveals that SARS-CoV-2-associated coagulopathy exists in almost all critically ill COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…All twelve studies were prospective observational and published between 1993 and 2021. Five studies were conducted in North America [ 28 , 31 , 33 , 35 , 37 ], four in Eastern Asia [ 27 , 29 , 32 ] and three in Europe [ 30 , 34 , 38 ]. The number of participants across studies ranged from 48 to 971 [ 31 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Protein C levels were measured using two different biochemical techniques. Five studies used antibody-based techniques, such as ELISAs [ 28 , 31 , 33 , 35 , 37 ], while the remainder of studies measured PC using functional clotting assays [ 27 , 29 , 30 , 32 , 35 , 36 ]. All studies reported their PC measurements as a percentage of healthy PC levels, with the exception of Shapiro et al, which reported PC measurements in ug/mL [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations